The Effect of Eight Weeks of Strength and Balance Training on Kinetic Variables in Elderly - Mahboobeh Dehnavi; Amirali Jafarnejadgero; Farhad Tabatabai Ghomsheh; Ali Fattahi (Caspian Journal of Neurological Sciences)
Background:  One of the most prevalent issues older people face is the decline in postural control. Addressing postural control is crucial for maintaining independence in older adults. Objectives: This study aimed to compare the effect of strength and balance training on kinetic variables and postural control of healthy older people. Materials & Methods: The current research includes two experimental groups (strength and balance training groups) and one control group. The statistical sample of this research included 36 people (12 people in each group) with an age range of 60 to 75 years. The force plate was used to evaluate the kinetic variables and postural control of older people. Results: Balance and strength training significantly affect the center of pressure in older people’s anterior-posterior (P=0.001) and medial-lateral directions (P=0.001). The results of the research also showed no significant difference between balance and strength training regarding the center of pressure in the anterior-posterior (P>0.05) and medial-lateral directions (P>0.05) of the older people. Conclusion: Both balance and strength training significantly impact the postural control of older people. Additionally, the results indicate no significant difference between balance and strength training in terms of their effects on the postural control of older adults. Therefore, balance and strength training can be used as an alternative to improve the postural control of older people and thus reduce their risk of falls.